2006
DOI: 10.1016/j.jalgebra.2005.06.022
|View full text |Cite
|
Sign up to set email alerts
|

A Lie algebra method for rational parametrization of Severi–Brauer surfaces

Abstract: It is well known that a Severi-Brauer surface has a rational point if and only if it is isomorphic to the projective plane. Given a Severi-Brauer surface, we study the problem to decide whether such an isomorphism to the projective plane, or such a rational point, does exist; and to construct such an isomorphism or such a point in the affirmative case. We give an algorithm using Lie algebra techniques. The algorithm has been implemented in Magma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…For higher genus we have written an experimental version of ConvertScroll in Magma, which can be found in the file convertscroll.m. It blindly relies on Schicho's function ParametrizeScroll, which implements the Lie algebra method from [18]. Unfortunately the latter is only guaranteed to work in characteristic zero, and indeed one runs into trouble when naively applying ParametrizeScroll over finite fields of very small characteristic; empirically however, we found that p > g suffices for a slight modification of ParametrizeScroll to work consistently.…”
Section: Methodsmentioning
confidence: 92%
“…For higher genus we have written an experimental version of ConvertScroll in Magma, which can be found in the file convertscroll.m. It blindly relies on Schicho's function ParametrizeScroll, which implements the Lie algebra method from [18]. Unfortunately the latter is only guaranteed to work in characteristic zero, and indeed one runs into trouble when naively applying ParametrizeScroll over finite fields of very small characteristic; empirically however, we found that p > g suffices for a slight modification of ParametrizeScroll to work consistently.…”
Section: Methodsmentioning
confidence: 92%
“…We then search for a zero-divisor in A by looking at short vectors in this lattice. Once a zero-divisor is found, it is easy to find an isomorphism A ∼ = Mat 3 (K), as described for example in [19,Section 5]. In [11, Paper III, Section 6] it is shown that if K = Q then the shortest vector in the lattice is a zero-divisor.…”
Section: Global Computationsmentioning
confidence: 99%
“…The problem of trivialising an n × n matrix algebra (that is, given structure constants for an L-algebra known to be isomorphic to Mat n (L), find such an isomorphism explicitly) is equivalent in the case n = 2 to solving a conic. For n > 2, this problem has been studied in [19,Section 5], [11,Paper III,Section 6], [24], with the result that practical algorithms are available if both n and the discriminant of the number field L are sufficiently small. However, since for us L is the field of definition of a 3-torsion point (which typically has degree 8), we have so far only been able to compute a few small examples.…”
Section: Introductionmentioning
confidence: 99%
“…Since our methods are of independent interest, we have made this section self-contained. For instance our methods could be used to improve the algorithm in [29] for parametrising Brauer-Severi surfaces.…”
Section: Introductionmentioning
confidence: 99%